2016
DOI: 10.1108/jmp-03-2014-0100
|View full text |Cite
|
Sign up to set email alerts
|

Overwork climate scale: psychometric properties and relationships with working hard

Abstract: Purpose-The purpose of this paper is to evaluate whether employees' tendency to work excessive hours is motivated by the perception of a work environment that encourages overwork (overwork climate). Thus, this study introduces a self-report questionnaire aimed at assessing the perception of a psychological climate for overwork in the workplace. Design/methodology/approach-In Study 1, the overwork climate scale (OWCS) was developed and evaluated using principal component analysis (n ¼ 395) and confirmatory fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 32 publications
7
66
0
7
Order By: Relevance
“…Very Low) profiles. Our results thus suggest that job resources might only minimally limit workaholism and suggest that caution is needed in the provision of hierarchical support, as this source of support tends to be associated with higher than average levels of workaholism (also see Mazzetti et al ., ). Future research needs to more extensively look at positive workplace characteristics that might curb workaholism, and try to unpack the mechanisms underlying the positive relation between hierarchical support and workaholism.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Very Low) profiles. Our results thus suggest that job resources might only minimally limit workaholism and suggest that caution is needed in the provision of hierarchical support, as this source of support tends to be associated with higher than average levels of workaholism (also see Mazzetti et al ., ). Future research needs to more extensively look at positive workplace characteristics that might curb workaholism, and try to unpack the mechanisms underlying the positive relation between hierarchical support and workaholism.…”
Section: Discussionmentioning
confidence: 97%
“…Prior variable‐centred (Mazzetti et al ., ; Sandrin & Gillet, ) and cluster analytic (Schaufeli, Bakker et al ., ) studies generally suggested that it might be important to distinguish the two facets of workaholism. For instance, Huyghebaert et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In future studies, engaging leadership could be measured intersubjectively by using 360° assessment. The same applies for work engagement (see Mazetti, Schaufeli, Guglielmi, & Depolo, ).…”
Section: Discussionmentioning
confidence: 98%
“…Overwork climate was assessed with a recently developed 8-item questionnaire (Mazetti, Schaufeli, Guglielmi & Depolo, 2016). An example item is: "In the organization where I work it is considered normal for employees to take their work home".…”
Section: Methodsmentioning
confidence: 99%